Development and assessment of the effectiveness of a courseware entitled Solat Jamaâ Dan Qasarâ Islamic Education For Secondary Two KBSM - Junaidi, Juhazren; Ali, Mohd. Fadzli; Aris, Baharuddin (2006)
Today, the influence of the rapidly growth of Information Technology has widely affected the field of education. The technology has enabled learning process through computers which is known as Computer Based Learning. In line with the Malaysian government's aspiration to bring up â€˜smart school, this project intends to view the effectiveness of a courseware entitled â€˜Solat Jamaâ dan Qasarâ Islamic Education based on the syllabus of Islamic Education for secondary two KBSM. This local oriented courseware was developed with the aim to assist students learning process in the topic of â€˜Solat Jamaâ€™ dan Qasarâ€™ at schools. The courseware is developed by implementing multimedia elements referring to the Hannafin & Peck (1985) development model. The cognitive learning theory which was applied to the courseware has the high potential to enhance studentsâ€™ thinking and perception making abilities. The effectiveness of the courseware is tested with the Quasi-Experimental research design using 15 samples involved in the pre and post tests. Instruments such as tests, questionnaires and observation are utilised to obtain data. Findings are then analysed using the Statistical Package For Social Science (SPSS) version 11.0 for Windows. The findings could also be useful for further researches. It is hoped that Computer Based Learning would be among the popular approaches in Islamic Education.